Open Learning and Technology: Problems and Potentials. - Danaher, P. A. (Social Alternatives)
This article focuses on the possibilities of utilizing educational technologies in an open learning approach to education. Open learning is an approach rather than a system or technique; it is based on the needs of individual learners, not the interests of the teacher or the institution; it gives students as much control as possible over what and when and where and how they learn; it commonly uses the delivery methods of distance education and the facilities of educational technology; it changes the role of a teacher from a source of knowledge to a manager of learning and a facilitator. It justifies these measures by arguments of efficiency, cost-effectiveness and equity. Advantage claimed for the new educational technologies is their capacity to enhance access to formal education for individuals and groups who would otherwise be prevented from participating. These individuals and groups are generally faced with the barrier of distance, such as living in a remote location or being required by time commitments to remain at home.